Pengaruh Kemampuan Literasi Terhadap Hasil Belajar Siswa Sekolah Menengah Kejuruan - Kurniawan, Reyhan; Muskhir, Mukhlidi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research aims to evaluate the relationship between student learning outcomes in the Basics of Electricity class X SMK N 1 Bukittinggi with 8 aspects of literacy abilities. Observation results show that the majority of students have relatively low literacy skills. Most people think that literacy is the key to forming human resources that can compete in the global market. This research aims to analyze the influence of the level of literacy skills on student learning outcomes in the Basics of Electricity subject in Class X SMKN 1 Bukittinggi. Class X students were the subjects of this research. The results of this research can provide a better understanding of the influence of 8 aspects of student literacy skills in the Basic Electricity subject at SMKN 1 Bukittinggi. This information can be used as a reference for developing more effective learning strategies and improving the curriculum to meet student needs. It is hoped that this research can increase awareness of the importance of students' literacy skills in the Basics of Electricity subject and provide suggestions to schools for improving and developing learning. Apart from that, this research can also contribute to previous research in the field of literacy and electricity education. Thus, this research is very relevant and important in efforts to improve the quality of learning and student literacy skills in the Basic Electricity subject at SMKN 1 Bukittinggi.